Nonlinear control of hydraulic robots. - Sirouspour, M.R (IEEE Transactions on robotics and automation)
This paper addresses the control problem of hydraulic robot manipulators. The backstepping design methodology is adopted to develop a novel nonlinear position tracking controller. The tracking errors are shown to be exponentially stable under the proposed control law. The controller is further augmented with adaptation laws to compensate for parametric uncertainties in the system dynamics. Acceleration feedback is avoided by using two new adaptive and robust sliding-type observers. The adaptive controllers are proven to be asymptotically stable via Lyapunov analysis. Simulation and experimental results performed with a hydraulic Stewart platform demonstrate the effectiveness of the approach